The role of interfacial properties on the intralaminar and interlaminar damage behaviour of unidirectional composite laminates: Experimental characterization and multiscale modelling. (1st April 2018) - Tan, W.; Naya, F.; Yang, L.; Chang, T.; Falzon, B.G.; Zhan, L.; Molina-Aldareguía, J.M.; González, C.; Llorca, J.
Abstract: The development of the latest generation of wide-body passenger aircraft has heralded a new era in the utilisation of carbon-fibre composite materials. One of the primary challenges facing future development programmes is the desire to reduce the extent of physical testing, required as part of the certification process, by adopting a 'certification by simulation' approach. A hierarchical bottom-up multiscale simulation scheme can be an efficient approach that takes advantage of the natural separation of length scales between different entities (fibre/matrix, ply, laminate and component) in composite structures. In this work, composites with various fibre/matrix and interlaminar interfacial properties were fabricated using an autoclave under curing pressures ranging from 0 to 0.8 MPa. The microstructure (mainly void content and spatial distribution) and the mechanical properties of the matrix and fibre/matrix interface were measured, the latter by means of nanoindentation tests in matrix pockets, and fibre push-in tests. In addition, the macroscopic interlaminar shear strength was determined by means of three-points bend tests on short beams. To understand the influence of interfacial properties on the intralaminar failure behaviour, a high-fidelity microscale computational model is presented to predict homogenized ply properties under shear loading. Predicted ply material parameters are then transferred to a mesoscale composite damage model to reveal the interaction between intralaminar and interlaminar damage behaviour of composite laminates.